Sistem Pendukung Keputusan Penentuan Bonus Karyawan Dengan Metode SAW Pada PT. Delima Makmur Aceh Singkil - Yulisman Yulisman; Refni Wahyuni (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Decision Support System (SPK) becomes a system that is always needed for companies in determining a decision, one of which is in determining the annual bonus for employees. PT. Delima Makmur Aceh Singkil in determining employee bonuses every year is still processed manually and assisted by the number and letter processing application, so the results of the calculation of employees who receive bonuses often do not match the criteria and performance of the employee. Bonus calculation results often affect the personal relationship between employees and managers or superiors. Regarding the problems needed a decision support system that can result in proper and transparent decisions in determining employees who receive annual bonuses from the company. The method used in the process of calculating bonus determination is the Simple Additive Weighting (SAW) method. The system making model uses a waterfall model and the system design model used is UML. The programming language used in making systems is PHP (Hypertext Preprocessor), and MySQL as a database, and system testing with the Black Box testing method. The results of the study are the SPK system makes it easier for companies in the assessment process and calculation of employee bonus determination in accordance with employee criteria and performance. This SPK system can provide transparent assessments and calculations in determining the bonus received by employees